Networks of outrage and hope: social movements in the internet age. Second edition enlarged and updated - Castells, Manuel (Cambridge, 2015)
"Networks of Outrage and Hope is an exploration of the new forms of social movements and protests that are erupting in the world today, from the Arab uprisings to the indignadas movement in Spain, from the Occupy Wall Street movement to the social protests in Turkey, Brazil and elsewhere. While these and similar social movements differ in many important ways, there is one thing they share in common: they are all interwoven inextricably with the creation of autonomous communication networks supported by the Internet and wireless communication.